Sergeant on stamp duties and companies capital duty - Sims, Bernard John.; Sims, E. M. E.; Tavaré, A. K. (London : Butterworths, 1972)
Since the last editions, there have been many changes, both in the substantive law and the practice of stamp duty. These changes have been in the process of continued rationalization and simplification of the stamp laws.
First ed. published in 1939 under title: The law of stamp duties.
Includes index.
ne 22/01/2019
Loans
Keywords: Stamp duties; Corporations